Oxford international secondary science for grade 7 - Fullick, Ann (Karachi: Oxford University Press., 2024)
Oxford International Secondary Science for Grade 7 is an engaging textbook that delves into key scientific concepts across various fields, including biology, chemistry, physics, and Earth sciences. Designed to foster inquiry-based learning, the book encourages students to think critically, conduct experiments, and apply their knowledge to real-world situations. Each chapter presents clear explanations, diagrams, and illustrations to enhance understanding, along with hands-on activities and questions that promote exploration and discussion. By integrating interdisciplinary approaches and practical applications, this textbook provides a solid foundation in science, preparing students for advanced studies and fostering a lifelong interest in the subject.